Glutathione in Ovarian Cancer - Nunes, Sofia C. (2018)
This research group is supported by Fundação para a Ciência e Tecnologia (FCT) (PhD ProRegeM program, PD/BD/105893/2014, FCT fellowship, PD/BD/105768/2014). iNOVA4Health—UID/Multi/04462/2013, a program financially supported by Fundação para a Ciência e Tecnologia / Ministério da Educação e Ciência, through national funds and co-funded by FEDER under the PT2020 Partnership Agreement is acknowledged.